The Optimazing to use of Artificial Intelegence in the Development of Teaching Materials for Marketing Management Course Based on Gedget Application - Saragih, Lenti Susanna; Darma, Jufri; Nurani, Sabda Dian (East Asian Journal of Multidisciplinary Research, 2025)
This study analyze the practicality of digitizing teaching materials and utilizing gadgets to assess learning in artificial intelligence marketing management courses. The study was conducted at the Faculty of Economics, Universitas Negeri Medan and included 65 respondents as a research sample obtained using purposive sampling method. The development methodology used is DDD-E model. The data collection methods used are observation, literature review, and questionnaire. The research data was then analyzed using descriptive qualitative analysis. The results of this study show that the teaching materials and learning assessment of artificial intelligence marketing management course based on gadget applications are actually applied, which can be seen from the calculation results of each survey indicator measured from the aspects of ease of use of the application, ease of use of the application, time efficiency of using the application, and innovation level of the application